The American Economy from Roosevelt to Trump - Valli, Vittorio (Springer International Publishing, 2018)
'This is essential reading for anybody interested in global history.' -Professor Ugo Panizza, The Graduate Institute of Geneva, Switzerland This illuminating book offers a compact survey and new interpretation of trends and policies in the US economy from the end of the nineteenth century to the initial period of the Trump administration. Valli maps three stages in this period of US economic history: first, the economic and demographic consequences of the frontier; second, the Fordist model of growth; and third, the attempt to build an economic empire through economic and financial globalization, military and political power and rapid technological progress. Examining pivotal moments from the Wall Street Crash and the World Wars to the recent Great Recession, Obamacare and Trump's electoral promises and first controversial decisions, this book is essential reading for all those interested in American economic power and its future. Vittorio Valli is Emeritus Professor at the University of Turin and has taught at Bocconi University and at the University of Padua, all in Italy. He has been Visiting Professor at the University of Kyoto, Japan; Seoul National University, South Korea; University of Nice, France; and Visiting Scholar at Brown University and the University of California (Berkeley), USA. He was the first president of the Italian Association for the Study of Comparative Economic Systems and the European Association of Comparative Economic Studies. He was also co-editor of the European Journal of Comparative Economics.